Preparation of ceramic support from waste: effect of sintering temperature: article / Nashrah Ayna Shah Fiesal and Dr. Norliza Ibrahim - Shah Fiesal, Nashrah Ayna; Ibrahim, Dr Norliza (2017)
A structure of ceramic support was fabricated from broken ceramic waste. The ceramic wastes which contain high source of alumina and silica were initially crushed into powders. The powders were mixed with binders and formed into cylindrical pellets. The preparation of the support was carried out based on press molding or compaction technique at a pressure of 160MPa. In this study, the effects of sintering temperatures were investigated by evaluating the phase characterization, porosity properties of the supports, average pore size and microstructure of the sintered samples. Sintering temperatures were carried out in a range of 900 to 1200℃ with an interval of 100℃ for 2.5 hours. The evaluation was carried out through the use of X-ray diffraction (XRD) and scanning electron microscopy (SEM). Based on the analysis, major crystalline phase of the sintered samples was mullite. However, fewer peaks were detected at 1200℃ resulting to a decrease in the mullite crystal phase. Results from sintering showed that, with increasing of temperature, open porosity showed a decrease trend in the sintered samples from 45.32% to 14.67% at 1200℃. Also, with increasing sintering temperature, average pore size increases with a maximum average of 17.04 µm at the final sintering temperature of 1200℃. On the other hand, SEM observation on microstructure of the sintered samples showed higher densification at 1200 ℃ compared to the other temperatures.